UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BUAH MAHKOTA DEWA (Phaleria macrocarpa) TERHADAP STAPHYLOCOCCUS AUREUS - Yunilda Rosa; Desti Yulistiana (STIK SITI KHADIJAH PALEMBANG, 2019)
Phaleria macrocarpa is one of the medicinal plants that many people use as a traditional medicinal which has many benefits, one of which is as a medicine for skin diseases. The content of flavonoid compounds in Phaleria macrocarpa believed to have potential as an antibacterial. The purpose of this study was to know the antibacterial activity of the ethanol extract of the Phaleria macrocarpa to inhibized Staphylococcus aureus bacteria. This research is an experimental study carried out by the liquid dilution method (KHM)and disk diffusion (KBM) of the extract of the Phaleria macrocarpa is divided into 6 concentrations namely 5%, 10% and 15% (KHM) and 40%, 50% and 60% (KBM). The positive control used is clindamycin and the negative control is aquadest. Data analysis uses univariate. Based on observations of the minimum inhibitory concentration of the extract of the fruit of the Phaleria macrocarpa which is at of 15%, while the minimum killed concentration is formed at of 40% with an average of 6.36 mm, and an average of zones formed on the positive control of 9.53 mm. From the results of the study, it was concluded that the extract of the fruit of the Phaleria macrocarpa can inhibit and kill the growth of Staphylococcus aureus bacteria.